The Structure and Function of Plastids - Wise, Robert R.; Hoober, J. Kenneth (Advances in Photosynthesis and Respiration, Including Bioenergy and Related Processes, 2006)
This volume provides a comprehensive look at the biology of plastids, the multifunctional biosynthetic factories that are unique to plants and algae. Fifty-six international experts have contributed 28 chapters that cover all aspects of this large and diverse family of plant and algal organelles. The book is divided into five sections: (I): Plastid Origin and Development; (II): The Plastid Genome and Its Interaction with the Nuclear Genome; (III): Photosynthetic Metabolism in Plastids; (IV): Non-Photosynthetic Metabolism in Plastids; (V): Plastid Differentiation and Response to Environmental Factors. Each chapter includes an integrated view of plant biology from the standpoint of the plastid. The book is intended for a wide audience, but is specifically designed for advanced undergraduate and graduate students and scientists in the fields of photosynthesis, biochemistry, molecular biology, physiology, and plant biology.